2022
DOI: 10.3390/nu14235158
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Gut Microbiota in Small for Gestational Age Infants with Very Low Birth Weight

Abstract: Small for gestational age (SGA) birth is associated with high rates of mortality and morbidity in preterm infants. The aim of this preliminary observational study was to investigate the difference in gut microbiota between SGA and appropriate for gestational age (AGA) preterm infants with very low birth weight (VLBW). We included 20 VLBW preterm infants (SGA, n = 10; AGA, n = 10) in this study. Stool samples were collected on days 7, 14, and 30 after birth. We performed 16S ribosomal DNA sequencing to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Maternal gut microbiota composition and metabolic activity differ before and during pregnancy [24,25]. Numerous studies have suggested associations between the compositions of maternal [26] and/or infant [27,28] gut microbiota and adverse fetal outcomes in many populations. For example, Ruminococcaceae, Lachnospiraceae, and Eubacteriaceae families identified from maternal fecal samples during pregnancy were important predictors of neonatal birth weight and weight at 1 month; Ruminococcaceae, Lachnospiraceae, Eubacteriaceae families, Prevotella copri, and Slackia isoflavoniconvertents were associated with gestational age in the rural Zimbabwe cohort [26].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal gut microbiota composition and metabolic activity differ before and during pregnancy [24,25]. Numerous studies have suggested associations between the compositions of maternal [26] and/or infant [27,28] gut microbiota and adverse fetal outcomes in many populations. For example, Ruminococcaceae, Lachnospiraceae, and Eubacteriaceae families identified from maternal fecal samples during pregnancy were important predictors of neonatal birth weight and weight at 1 month; Ruminococcaceae, Lachnospiraceae, Eubacteriaceae families, Prevotella copri, and Slackia isoflavoniconvertents were associated with gestational age in the rural Zimbabwe cohort [26].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, stressors associated with neonatal life in the hospital, such as frequent antibiotic usage, invasive procedures, and maternal separation, can all lead to dysbiosis ( 40 ). A small cohort study discovered that SGA newborns had smaller abundances of Klebsiella and Enterobacter than AGA infants, and the Beta diversity of bacterial community structure began to segregate at postnatal day 30 ( 41 ). Transcriptome investigations of the SGA rat model revealed that IGF-2 expression was considerably reduced in CUG (catch-up growth)-SGA rats, which was associated with a decrease in lactic acid bacteria ( 42 ).…”
Section: Gut Microbiota and Linear Growthmentioning
confidence: 99%
“…In summary, the maternal microbiota is directly linked to the health of the baby, and its disruption can result in fetal growth and development abnormalities such as premature birth, SGA newborns, and macrosomia. Genetic variables ( 20 ), nutrition before and during pregnancy ( 30 ), manner of birth ( 36 ), and gestational age at birth ( 41 ) all influence baby microbiome colonization. Lactobacillus and Bifidobacterium have been shown to promote fetal growth, but pathogenic bacteria such as Shigella , Ralstonia , and Clostridium have been found to inhibit baby growth ( 29 , 39 ).…”
Section: Gut Microbiota and Linear Growthmentioning
confidence: 99%
See 2 more Smart Citations